Students’ Opinion on Compulsory Distance Learning at the Pedagogical University of Krakow - Musiał, Emilia (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The coronavirus pandemic has introduced a number of restrictions. One of them was the closure of schools, educational institutions and universities. Compulsory distance learning has started, including at the university level. Until now, distance education in Poland has been treated at state universities as an unimportant addition to the mainstream of education. However, the time of the pandemic changed this situation radically, whether the universities wanted it or not, they had to start - practically overnight - the process of transition from traditional to distance education. And, which raises the question: how the time of “emergency” education during a pandemic was used by the academic community. What did the didactic everyday life at the Pedagogical University look like, in connection with the suspension of classes for universities and, consequently, for students? What was the opinion of students about distance learning within the “walls” of our university? Have the students dealt with the new challenge? Finally, what were the most common problems they faced in teaching during a pandemic using available distance learning methods and techniques? These and other issues related to universal distane education in the era of coronavirus were asked - in order to verify their opinion - students of the Pedagogical University of Krakow. The aim of the study was distance education seen through the eyes of students and their assessment of distance learning.